Penerapan Terapi Puzzle untuk Meningkatkan Fungsi Kognitif pada Lansia Demensia di Panti Jompo Taman Bodhi Asri - Martina, Siska Evi; Gultom, Rumondang; Sinaga, Janno; Zalukhu, Citiek Sundari; Saragi, Estovani Jesica Titania; Sigalingging, Evelyn Ruth Sani; Zega, Fitri Laras Martanti Br.; Zefanny, Glori Feby; Sarumaha, Mae’Ulida; Panjaitan, Manahan Batistuta; Putra, Reza Pratama (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
Dementia is a condition characterized by a decline in memory and cognitive abilities. If left unaddressed, it can result in behavioral changes in the elderly, such as impaired memory, loss of self-recognition, reduced self-care, and hostility toward others. Puzzle therapy involves assembling images that have been divided into pieces, aiming to stimulate cognitive function, train patience, and foster social skills. This group activity therapy was conducted to assess the memory of elderly individuals with dementia. The intervention involved nine elderly participants diagnosed with dementia. Data were collected using the MOCA INA questionnaire and standard operating procedures for puzzle activities. It is recommended that puzzle therapy be implemented regularly for elderly individuals experiencing dementia.